2016
DOI: 10.1007/s12609-016-0216-5
|View full text |Cite
|
Sign up to set email alerts
|

Physician and Patient Barriers to Breast Cancer Preventive Therapy

Abstract: The uptake of selective estrogen receptor modulators (SERMs) and aromatase inhibitors (AIs) for the primary prevention of breast cancer is low, despite their proven efficacy in several randomized clinical trials. This review summarizes the latest data on physicians’ and women’s barriers to breast cancer preventive therapy. Physicians’ challenges include: identifying suitable candidates for preventive therapy, inadequate training and confidence in risk assessment and counselling, insufficient knowledge of risk-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 49 publications
(117 reference statements)
0
33
0
Order By: Relevance
“…52 Clinicians also need to be educated on risk/benefit counseling, since lack of physician knowledge has been cited as an important factor for low rates of chemoprevention uptake. 53,54 The American Society of Clinical Oncology guideline strongly recommends that chemoprevention should be discussed for women with a 5-year projected absolute risk of breast cancer of 1.66% or higher. 55 NCCN guidelines use the same threshold of a 5-year risk of 1.7% or higher, but adds that patients should have at least a life expectancy of 10 years or longer to be considered for preventive treatment.…”
Section: Map3 and Ibis-ii Performed Subgroup Analysis Of Women Withmentioning
confidence: 99%
“…52 Clinicians also need to be educated on risk/benefit counseling, since lack of physician knowledge has been cited as an important factor for low rates of chemoprevention uptake. 53,54 The American Society of Clinical Oncology guideline strongly recommends that chemoprevention should be discussed for women with a 5-year projected absolute risk of breast cancer of 1.66% or higher. 55 NCCN guidelines use the same threshold of a 5-year risk of 1.7% or higher, but adds that patients should have at least a life expectancy of 10 years or longer to be considered for preventive treatment.…”
Section: Map3 and Ibis-ii Performed Subgroup Analysis Of Women Withmentioning
confidence: 99%
“…The most commonly cited reasons by patients for declining preventive therapy are fear of side effects, including endometrial cancer, thromboembolic disease, and menopausal symptoms (22,23,28). Indeed, we found that concern about side effects was the primary reason for declining preventive therapy in addition to other previously reported barriers such as having an aversion to additional medications (29) and risk of breast cancer not perceived to be sufficiently high (30).…”
Section: Discussionmentioning
confidence: 57%
“…Barriers to prescribing preventive therapy that have been reported by primary care providers include lack of knowledge about preventive options, lack of time with patients, and lack of training in risk/benefit counseling (21)(22)(23). Paradoxically, risk/benefit counseling has been shown to reduce the uptake of preventive therapy (15) presumably by causing women to overestimate the risks of treatment (24).…”
Section: Discussionmentioning
confidence: 99%
“…Women without surgical excision who did not undergo a surgical consultation had significantly lower imaging adherence as well as chemoprevention uptake compared with their counterparts who underwent surgery, suggesting an important role for specialist care in these women with elevated risk. uptake rates in the literature (5%-15%) (36,37). In addition to unfavorable side-effect profiles of chemopreventive agents, a previously cited major barrier to implementation of chemoprevention was "lack of confidence in identifying high-risk patients" among nonspecialist care providers, with only 8% family physicians and 9% internists reporting ever having recommended or prescribed preventive therapy despite known risk factors (36).…”
Section: Discussionmentioning
confidence: 99%
“…uptake rates in the literature (5%-15%) (36,37). In addition to unfavorable side-effect profiles of chemopreventive agents, a previously cited major barrier to implementation of chemoprevention was "lack of confidence in identifying high-risk patients" among nonspecialist care providers, with only 8% family physicians and 9% internists reporting ever having recommended or prescribed preventive therapy despite known risk factors (36). In our study, the surgical group (ie, those who underwent surgical consultation) was significantly more likely to take up chemoprevention than the nonsurgical group, and all 21 women who chose chemoprevention had a surgical consultation, suggesting further value in breast specialist consultation for these women.…”
Section: Discussionmentioning
confidence: 99%